Accounting for Forward Rates in Markets for Foreign Currency. - Backus, David K; Gregory, Allan W; Telmer, Chris I (Journal of Finance, 1993)
Forward and spot exchange rates between major currencies imply large standard deviations of both predictable returns from currency speculation and of the equilibrium price measure (the intertemporal marginal rate of substitution). Representative agent theory with time-additive preferences cannot account for either of these properties. The authors show that the theory does considerably better along these dimensions when the representative agent's preferences exhibit habit persistence but that the theory fails to reproduce some of the other properties of the data–in particular, the strong autocorrelation of forward premiums.